Review: High-Entropy Materials for Lithium-Ion Battery Electrodes - Sturman, James W.; Baranova, Elena A.; Abu-Lebdeh, Yaser (Frontiers in Energy Research, 2022)
The lithium-ion battery is a type of rechargeable power source with applications in portable electronics and electric vehicles. There is a thrust in the industry to increase the capacity of electrode materials and hence the energy density of the battery. The high-entropy (HE) concept is one strategy that may allow for the compositional variability needed to design new materials for next-generation batteries. Inspired by HE-alloys, HE-oxides are an emerging class of multicomponent ceramics with promising electrochemical properties. This review will focus on the application of these materials to the development of new battery electrodes with insight into the materials’ structure/property relationship and battery performance. We highlight recent results on HE-oxides for the cathode and anode. In addition, we discuss some emerging results on HE-solid electrolytes and HE-alloy anodes.